PROCES WYCHOWANIA UCZNIÓW WOJSKOWYCH KLAS MUNDUROWYCH NA PRZYKŁADZIE ZESPOŁU SZKÓŁ EKONOMICZNYCH I MUNDUROWYCH IM. GEN. WŁADYSŁAWA ANDERSA W CHEŁMIE - Turchin, T.; Bejger, H.; Łubkowski, R. (НДУ імені Миколи Гоголя, 2020)
The article is devoted to the topical problem of military-patriotic education of student youth and its preparation for the defense of the Motherland. The authors analyze the theoretical and practical aspects of the problem of forming the patriotism of the younger generation of military classes in the process of studying the subject "Military Education". Attention is drawn to the lack of effectiveness of traditional forms and means of military-patriotic education and a number of their own proposals to increase the level of military-patriotic education of military students in the study of the subject "Military Education". The content and significance of the Certified Military Classes project, which expands the educational offer for young people interested in various career paths related to the army and is designed to prepare young men and women for military service. The analysis and results of experimental researches on formation of readiness of student’s youth for service in army are presented, the existing contradictions are described and search of new scientific and methodical approaches is carried out. In particular, military family traditions, motives for choosing a military class, life goals of young people and professional plans for the future of military class students, etc. were studied.
Keywords: formation of patriotism; students of military classes; motives of choice; life goals and readiness of student youth for service in the army